A Pilot Study of the Efficacy and Economical Sustainability of Acute Coronavirus Disease 2019 Patient Management in an Outpatient Setting - De Lorenzo, Rebecca; Montagna, Marco; Bossi, Eleonora; Vitali, Giordano; Taino, Alba; Cilla, Marta; Pata, Giulia; Lazorova, Ludmilla; Pesenti, Riccardo; Pomaranzi, Chiara; Bussolari, Cecilia; Martinenghi, Sabina; et al. (Frontiers in Medicine, 2022)
Objective: To report a preliminary experience of outpatient management of patients with COVID-19 through an innovative approach of healthcare delivery. Patients and Methods: Patients evaluated at the Mild-to-Moderate COVID-19 Outpatient clinics (MMCO) of San Raffaele University Hospital and Luigi Sacco University Hospital in Milan, Italy, from 1 October 2020 to 31 October 2021 were included. Patients were referred by general practitioners (GPs), Emergency Department (ED) physicians or hospital specialists (HS) in case of moderate COVID-19. A classification and regression tree (CART) model predicting ED referral by MMCO physicians was developed to aid GPs identify those deserving immediate ED admission. Cost-effectiveness analysis was also performed. Results: A total of 660 patients were included. The majority (70%) was referred by GPs, 21% by the ED and 9% by HS. Patients referred by GPs had more severe disease as assessed by peripheral oxygen saturation (SpO2), ratio of arterial oxygen partial pressure to fractional inspired oxygen (PaO2/FiO2), C-reactive protein (CRP) levels and interstitial involvement at lung ultrasound. Among them, 18% were addressed to the ED following MMCO assessment. CART analysis identified three independent predictors, namely home-measured SpO2, age and body mass index (BMI), that robustly divide patients into risk groups of COVID-19 severity. Home-measured SpO2 <95% and BMI ≥33 Kg/m2 defined the high-risk group. The model yielded an accuracy (95% CI) of 83 (77-88)%. Outpatient management of COVID-19 patients allowed the national healthcare system to spare 1,490,422.05 € when compared with inpatient care. Conclusion: MMCOs were effective and sustainable in managing COVID-19 patients and allowed to alleviate pressure on EDs and hospital wards, favouring effort redirection towards non-COVID-19 patients.